An unusual case of meat bolus impaction in an adult - Malhotra, Sonali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Esophageal food impaction is a common emergency faced by ENT surgeons and gastroenterologists. It is important to know what techniques and instruments are indicated for different situations. Endoscopic treatment is a reliable and safe procedure in skilled, expert hands with a high success rate and low morbidity and mortality.